Determination of performance degradation of a marine diesel engine by using curve based approach - Kokkulunk, Gorkem; Parlak, Adnan; Erdem, Hasan Huseyin (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
Nowadays, energy efficiency measures on ships are the top priority topic for the maritime sector. One of the important key parameters of energy efficiency is to find the useful tool to improve the energy efficiency. There are two steps to improve the energy efficiency on ships: Measurement and Evaluation of performance of main fuel consumers. Performance evaluation is the method that evaluates how much the performance changes owing to engine component degradation which cause to reduce the performance due to wear, fouling, mechanical problems, etc. In this study, zero dimensional two zone combustion model is developed and validated for two stroke marine diesel engine (MITSUI MAN B&W 6S50MC). The measurements are taken from a real ship named M/V Ince Inebolu by the research team during the normal operation of the main engine in the region of the Marmara Sea. To evaluate the performance, Curve based method is used to calculate the total performance degradation. This total degradation is classified as parameters of compression pressure, injection timing, injection pressure, scavenge air temperature and scavenge air pressure by means of developed mathematical model. In conclusion, the total degradation of the applied ship is found as 620 kW by power and 26.74 g/kW h by specific fuel consumption. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Degradation; Performance; Marine diesel engine; Two-stroke; Mathematical model; ZERO-DIMENSIONAL MODEL; EMISSION; TURBOCHARGER; SIMULATION; PREDICTION; PROPULSION; TDC; Thermodynamics; Energy & Fuels; Engineering; Mechanics